2018
DOI: 10.1002/etc.4220
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil porewater properties on the fate and toxicity of silver nanoparticles toCaenorhabditis elegans

Abstract: Engineered nanoparticles (NPs) entering the environment are subject to various transformations that in turn influence how particles are presented to, and taken up by, organisms. To understand the effect of soil properties on the toxicity of nanosilver to Caenorhabditis elegans, toxicity assays were performed in porewater extracts from natural soils with varying organic matter content and pH using 3-8 nm unfunctionalized silver (Ag 3-8Unf), 52-nm polyvinylpyrrolidone (PVP)-coated Ag NPs (Ag 52PVP), and AgNO as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the negative impact of the AgNPs on the soil microbial biomass after 60-day-incubation contrasts with the expected protective effect of the high organic matter content in these tropical soils. In detail, it has been suggested that organic matter and clays can complex to AgNPs, reducing their mobility and toxicity (Rahmatpour et al, 2017;Schultz et al, 2018). However, while this protective mechanism could have operated at the beginning of the incubation, the high organic matter content did not protect the bacterial, Gram+ and actinobacterial groups, from the harmful impact of the AgNPs in the long term, even at the low and realistic doses assayed here.…”
Section: Impact Of Agnps On Soil Physico-chemical Properties and Microbial Biomassmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the negative impact of the AgNPs on the soil microbial biomass after 60-day-incubation contrasts with the expected protective effect of the high organic matter content in these tropical soils. In detail, it has been suggested that organic matter and clays can complex to AgNPs, reducing their mobility and toxicity (Rahmatpour et al, 2017;Schultz et al, 2018). However, while this protective mechanism could have operated at the beginning of the incubation, the high organic matter content did not protect the bacterial, Gram+ and actinobacterial groups, from the harmful impact of the AgNPs in the long term, even at the low and realistic doses assayed here.…”
Section: Impact Of Agnps On Soil Physico-chemical Properties and Microbial Biomassmentioning
confidence: 70%
“…However, while this protective mechanism could have operated at the beginning of the incubation, the high organic matter content did not protect the bacterial, Gram+ and actinobacterial groups, from the harmful impact of the AgNPs in the long term, even at the low and realistic doses assayed here. This lack of protective effect could be due to a slow release of the Ag + ions from the AgNPs complexed to the organic matter and clays, and to the higher toxicity of Ag + when compared to AgNPs, as reported by other authors (Yang et al, 2013;Rahmatpour et al, 2017;Schultz et al, 2018).…”
Section: Impact Of Agnps On Soil Physico-chemical Properties and Microbial Biomassmentioning
confidence: 74%
“…The results exhibited the complex interactions between ENPs and plant roots in the rhizosphere soil because the poor fitting indicated that the selected invariables could not fully capture the relationship between the input and output and additional input variables are needed to describe the reactions in plant rhizosphere. Previous studies have shown that ENPs undergo homo- and heteroaggregation in soil pore water, attach to soil mineral particles, , and interact with soil microbial community, which reciprocally affect plant uptake of ENPs . To capture the effect of these physical, chemical, and biological processes, we added one more descriptor in the BPNN model in soil, the initial concentration of ENPs, because the interactions of ENPs with soil components are often concentration-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, the soil-to-soil solution ratio is higher than would be found in nonsaturated soils. However, in more concentrated soil solutions containing dissolved organic matter, dissolution in the extracted soil porewater (measured by assessing concentrations of Ag in 10-kDa ultrafiltrate) was also found to be low, further supporting the assertion that the presence of organic matter reduces the release of Ag + ions from Ag NMs in soil systems (Collin et al 2014;Schultz et al 2018). The soil porewater ultrafiltration and Ag measurements carried out at the end of the present study also showed low Ag concentrations in the ultrafiltrate, suggesting that low Ag + concentrations in the porewater indicate low rates of dissolution.…”
Section: Discussionmentioning
confidence: 63%